Lidar depolarization characterization using a reference system - Papetta, Alkistis; Marenco, Franco; Kezoudi, Maria; Mamouri, Rodanthi-Elisavet; Nisantzi, Argyro; Baars, Holger; Popovici, Ioana Elisabeta; Goloub, Philippe; Victori, Stéphane; Sciare, Jean (My University, 2024)
In this study, we present a new approach for the determination of polarization parameters of the Nicosia Cimel CE376 lidar system, using the PollyXT in Limassol as a reference instrument. The method is applied retrospectively to the measurements obtained during the 2021 Cyprus Fall Campaign. Lidar depolarization measurements represent valuable information for aerosol typing and for the quantification of some specific aerosol types such as dust and volcanic ash. An accurate characterization is required for quality measurements and to remove instrumental artifacts. In this article, we use the PollyXT, a widely used depolarization lidar, as our reference to evaluate the CE376 system's gain ratio and channel cross-talk. We use observations of transported dust from desert regions for this approach, with layers in the free troposphere. Above the boundary layer and the highest terrain elevation of the region, we can expect that, for long-range transport of aerosols, local effects should not affect the aerosol mixture enough for us to expect similar depolarization properties at the two stations (separated by 1/460km). Algebraic equations are used to derive polarization parameters from the comparison of the volume depolarization ratio measured by the two systems. The applied methodology offers a promising opportunity to evaluate the polarization parameters of a lidar system, in cases where a priori knowledge of the cross-talk parameters is not available, or to transfer the polarization parameters from one system to the other.
Keywords: parameter estimation; aerosol; etection method; lidar